กฎหมายความรับผิดในผลิตภัณฑ์ : รูปแบบที่เหมาะสมสำหรับประเทศไทย - มนต์ชัย ธาดาอำนวยชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This study investigated concept and development of foreign Product Liability Law and the problems of the enforcement of such Law in foreign countries and what would be the implication if this law is applied in Thailand, in order to find the appropriate pattern of Product Liability Law in Thailand. Results of the study indicated that in foreign, strict liability was originally applied in Product Liability case which left excessive accountability to business sector. Later, development of product liability law was divided into two systems; i.e. litigation which is based on strict liability rule and Product Liability insurance fund which must be sponsored by business sector and consumers participatively. This system could be used in combination with the litigation system by categorizing products that could create damages to consumers such as medical supplies, medicine, food, beverages, automobiles and setting up product liability insurance fund for these kinds of products which funded by business sector and consumers. This fund is the appropriate solution for not creating more liable to either parties. Though Product Liability Law will effect the price of product, consumers will have more confidence in product safety. In Thailand, a draft of Product Liability Law is under consideration. This study then tried to suggest the concept to apply the litigation system and Product Liability insurance fund in combination by seeking appropriate pattern for Product Liability Law in Thailand which author believed to be appropriate and fair for both business sectors and consumers.